2014
DOI: 10.1007/s10875-013-9978-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium massiliense Induces Inflammatory Responses in Macrophages Through Toll-Like Receptor 2 and c-Jun N-Terminal Kinase

Abstract: Mycobacterium massiliense (Mmass) is an emerging, rapidly growing mycobacterium (RGM) that belongs to the M. abscessus (Mabc) group, albeit clearly differentiated from Mabc. Compared with M. tuberculosis, a well-characterized human pathogen, the host innate immune response against Mmass infection is largely unknown. In this study, we show that Mmass robustly activates mRNA and protein expression of tumor necrosis factor (TNF)-α and interleukin (IL)-6 in murine bone marrow-derived macrophages (BMDMs). Toll-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Furthermore, we confirmed the HGMN2 knock‐down–mediated enhancement of NFκB activation contributes to the increased production of NO by using NFκB inhibitor. Additionally, Mycobacterium massiliense , belongs to the Mycobacterium.abscessus , has been reported to induce pro‐inflammatory cytokines (TNF‐α, IL‐6 and IL‐1β) dependent on JNK signalling not on ERK1/2 or p38 pathway in BMDMs . In our study, we found that HMGN2 knock‐down enhanced all the three signalling pathways, and we need further experiments to proof whether it was responsible for the HMGN2 regulated M1 markers genes expression.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, we confirmed the HGMN2 knock‐down–mediated enhancement of NFκB activation contributes to the increased production of NO by using NFκB inhibitor. Additionally, Mycobacterium massiliense , belongs to the Mycobacterium.abscessus , has been reported to induce pro‐inflammatory cytokines (TNF‐α, IL‐6 and IL‐1β) dependent on JNK signalling not on ERK1/2 or p38 pathway in BMDMs . In our study, we found that HMGN2 knock‐down enhanced all the three signalling pathways, and we need further experiments to proof whether it was responsible for the HMGN2 regulated M1 markers genes expression.…”
Section: Discussionmentioning
confidence: 60%
“…Since 2005, we were the first to reported that the HMGN2 can functionally as an antimicrobial molecule to against bacteria, 28 In order to investigate the functional relevance of the NTM-induced HMGN2 up-regulation, we firstly analysed the production 42 In our study, we found that HMGN2 knock-down enhanced all the three signalling pathways, and we need further experiments to proof whether it was responsible for the HMGN2 regulated M1 markers genes expression.…”
Section: Discussionmentioning
confidence: 82%
“…M. abscessus induces the secretion of tumor necrosis factor (TNF)-α, IL-6, and IL-12p40 in murine macrophages via Toll-like receptor (TLR)-2 [10] . In addition, M. massiliense induces TNF-α and IL-6 production in murine macrophages [11] . Peripheral blood mononuclear cells (PBMCs) from NTM patients were shown to produce less Th1 cytokines (IFN-γ, IL-12, and TNF-α) compared to healthy controls, suggesting that NTM lung disease might reflect defects in the IL-12/IFN-γ pathway [12] , [13] .…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have reported that mycobacteria and their antigenic components activate intracellular signaling cascade through innate recognition of TLRs ( 9 , 12 , 16 , 17 , 20 ). To determine the roles of TLR2 in mycobacteria-induced production of proinflammatory cytokines in macrophages, BMDMs from TLR2 wild type (WT) and knockout (KO) mice were stimulated with ATCC, 113S, or 114R strains of M. scrofulaceum in an MOI-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that mycobacterial infection induced phosphorylation of MAPK such as p38, JNK, and ERK1/2, resulting in production of inflammatory cytokines ( 16 , 20 ). To determine whether M. scrofulaceum -induced inflammatory responses were dependent on MAPK signaling, we monitored MAPK activation in macrophages.…”
Section: Resultsmentioning
confidence: 99%